Project QUIT (Quit Using Drugs Intervention Trial): a randomized controlled trial of a primary care‐based multi‐component brief intervention to reduce risky drug use. (November 2015) - Gelberg, Lillian; Andersen, Ronald M.; Afifi, Abdelmonem A.; Leake, Barbara D.; Arangua, Lisa; Vahidi, Mani; Singleton, Kyle; Yacenda‐Murphy, Julia; Shoptaw, Steve; Fleming, Michael F.; Baumeister, Sebastian E.
Abstract Aims To assess the effect of a multi‐component primary care delivered brief intervention for reducing risky psychoactive drug use (RDU) among patients identified by screening. Design Multicenter single‐blind two‐arm randomized controlled trial of patients enrolled from February 2011 to November 2012 with 3‐month follow‐up. Randomization and allocation to trial group were computer‐generated. Setting Primary care waiting rooms of five federally qualified health centers in Los Angeles County (LAC), USA. Participants A total of 334 adult primary care patients (171 intervention; 163 control) with RDU scores (4–26) on the World Health Organization (WHO) Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) self‐administered on tablet computers. 261 (78%) completed follow‐up. Mean age was 41.7 years; 62.9% were male; 37.7% were Caucasian. Intervention(s) and Measurement Intervention patients received brief (typically 3–4 minutes) clinician advice to quit/reduce their drug use reinforced by a video doctor message, health education booklet and up to two 20–30–minute follow‐up telephone drug use coaching sessions. Controls received usual care and cancer screening information. Primary outcome was patient self‐reported use of highest scoring drug (HSD) at follow‐up. Findings Intervention and control patients reported equivalent baseline HSD use at 3‐month follow‐up. After adjustment for covariates, in the complete sample linear regression model, intervention patients used their HSD on 3.5 fewer days in the previous month relative to controls (P<0.001), and in the completed sample model, intervention patients used their HSD 2.2 fewer days than controls (P < 0.005). No compensatory increases in use of other measured substances were found. Conclusions A primary‐care based, clinician‐delivered brief intervention with follow‐up coaching calls may decrease risky psychoactive drug use.